REGULATORY ENTITIES IN THE CHECK SYSTEM IN THE IMMIGRATION LAW FROM THE IMPOSITION OF IMMIGATION ADMINISTRATIVE MEASURES AGAINST THE CASE OF DJOKO CHANDRA - Ade Daud Iqbal; Anita Herlina (Journal of Law and Border Protection, 2021)
The traffic of people going out or entering the territory between countries has various kinds of impacts, these impacts can be god or bad for the region. Or in other cases even the citizens themselves who cause bad effects for their own country. Therefore, Immigration has regulations to deal with problems that come either from foreigners or Indonesian citizens themselves. One of them is regarding the administrative immigration action for anyone who violates the applicable laws and regulations. As for other regulations, with the existence of a Block or Prevention and Determination system that contains anyone who is refused entry or exit from Indonesian territory with a certain reason that is included in a list. Djoko Chandra. This shows that the immigration actions implemented by immigration must always be improved and carried out with full integrity in superior human resources and coordination between ministries / agencies that have authority.